ANALISIS PENINGKATAN PENDAPATAN KONTRIBUSI WANITA BAGI PENDAPATAN RUMAH TANGGA DALAM MEMANFAATKAN LAHAN PEKARANGAN DI DESA LEWALU KECAMATAN ALOR BARAT LAUT - Andri Permata Timung; Emirensiana Latuan; Amri Bali; Yustina Maro (Partner, 2023)
Optimizing land use needs to be done in hilly topographic areas requiring the use of yard land to increase household income. The research aims to determine the area of the yard, types of plants cultivated using the yard, and the income contribution to family income in Lewalu Village. This research is quantitative research with 50 respondents. Data analysis uses mean, income analysis, and proportion analysis. The research results show that: (1) the area of family yards in Lewalu Village is classified as medium because there are 64% of yards with an area of 120-400 m². (2) Variations in the use of the Lewalu Village yard include horticultural plants, food, secondary crops and spices; (3) income of the people of Lewalu Village by using the yard is IDR 79,600 with the contribution of farmers' income from using the yard to family income of 9.93% which is relatively low.Keywords: household income, land, women farmers, yard